Age at Menarche and Eating Pattern among High School Students in Jatinangor in 2013 - Fani Fitrya Nafisah; Insi Farisa Arya; Eppy Darmadi Achmad (Faculty of Medicine Universitas Padjadjaran, 2016)
Background: Age at menarche has notably declined over the past several decades; the fact is in line with the improvement of nutritional intake. Age at menarche can affect health outcomes in adulthood. This study aimed to describe the age at menarche and eating pattern among students in Jatinangor.Methods: Data were obtained from Survey of Adolescent Reproductive Health in Jatinangor in 2013 with total sampling technique. The sample criteria were data from students who had started their periodwhen the study was conducted. Dietary information was collected by eating pattern recall questionnaire and was taken by trained enumerators. Nutrient intakes and proportion of energy intake were divided into groups according to Recommended Dietary Allowance 2012.Results: In total, 59 data were analyzed. The age at menarche were ranged from 9 (n=1) to 15 (n=1). Most of students had their menarche at 12 (37.3%). Intake of energy (49.2%), protein (64.4%), fat (61%), and carbohydrate (54.2%) were mostly deficient, but the proportion of energy intake from fat (49.2%) and carbohydrate (66.1%) were mostly adequate. The student with youngest age at menarche had adequate energy intake, excess protein intake and excess proportion of energy intake from fat. Student with the oldest age had deficient energy, fat, and protein intake and excess proportion of energy intake from carbohydrate. Conclusions: This study shows that student with youngest age at menarche has different eating pattern compared to the oldest, while the others seem similar. [AMJ.2016;3(1):156–63] DOI: 10.15850/amj.v3n1.714